Facile synthesis of rGO–MoS2–Ag nanocomposites with long-term antimicrobial activities. (8th January 2020) - Li, Jingchen; Zheng, Jie; Yu, Yadong; Su, Zhen; Zhang, Lihui; Chen, Xiaojun
Abstract: The abuse of antibiotics has led to the emergence of numerous super resistant bacteria, which pose a serious threat to public health. Developing nanomaterials with novel modes of bactericidal activity offers the promise of fighting pathogens without the risk of causing drug resistances. Here, we used reduced graphene oxide (rGO), bulk molybdenum disulfide (MoS2 ) and silver nitrate (AgNO3 ) to synthesize a ternary nanocomposite, rGO–MoS2 –Ag, via a simple one-pot method. The resulting rGO–MoS2 –Ag presented as crumpled and sheet-like structures decorated with Ag nanoparticles. The minimum inhibitory concentration and minimum bactericidal concentration of rGO–MoS2 –Ag against Escherichia coli were 50 and 100 μ g ml −1, while Staphylococcus aureus reacted only to twice higher concentrations of 100 and 200 μ g ml −1, respectively. Notably, rGO–MoS2 –Ag exhibited better antibacterial activity towards E. coli and S. aureus than rGO, MoS2, or rGO–MoS2 . This result can be attributed to the excellent performance of rGO–MoS2 –Ag in destroying the bacterial cell membrane and inducing the generation of reactive oxygen species. The Ag + ion release of rGO–MoS2 –Ag was delayed, endowing the nanocomposite with long-term antibacterial capabilities and better biosafety. Our results indicate that the as-prepared rGO–MoS2 –Ag has promising potential for application in biomedicine and public health.